ASSESSING THE ACCURACY OF A LARGE OBSERVATIONAL REGISTRY OF NEOVASCULAR AGE-RELATED MACULAR DEGENERATION. Issue 5 (May 2020) - Nguyen, Vuong; Leung, King Fai Calvin; Nguyen, Chu Luan; Squirrell, David; Essex, Rohan; Arnold, Jennifer; Young, Stephanie; Barthelmes, Daniel; Gillies, Mark
Abstract : Purpose: To evaluate the accuracy of an observational database that tracks real-world treatment outcomes for neovascular age-related macular degeneration. Methods: We audited 245 randomly sampled eyes from 189 patients with 3, 356 visits from 11 doctors in the Fight Retinal Blindness! database. Sex, birth year, previous treatments received, treatment, and visual acuity were validated against the clinical notes. Error rates, the proportion of missed visits (the number of visits present in the patient record but not entered into Fight Retinal Blindness!), the level of agreement using Cohen's kappa (κ) and intraclass correlation coefficients, and positive and negative predictive values were calculated. A visual acuity error was defined as an absolute difference of ≥5 letters. Results: The overall error rate was 3.5% (95% confidence interval: 3.1–3.9). The error rate for visual acuity was 5.1% (95% confidence interval: 4.2–5.9) and <5% for the remaining fields. The level of agreement for each field ranged from good to excellent (κ or intraclass correlation ≥ 0.75). The positive predictive value and negative predictive value for visits were 99% and 89%, respectively. The proportion of missed visits was 10.2%. Conclusion: Accuracy of the Fight Retinal Blindness! database was good (>95%). The rate of missed visits was high, possibly due to the high burden of retrospective data entry or patients switching practitioners during treatment. Abstract : Observational health registries are a valuable source of real-world evidence to complement randomized clinical trials but are rarely validated. We found the accuracy of a large observational database for neovascular age-related macular degeneration to be high, but missing data could be an issue.